The Main Tasks of Biophysics and the Physical Foundations of Biological Structures - Kattaxodjayeva Dinara Utkurxodjayevna; Elmurotova Dilnoza Baxtiyorovna; Tanirbergenova Nurjamal Orazbaevna (American Journal of Bioscience and Clinical Integrity, 2025)
This paper presents widely used biophysical methods and key research areas. It also examines key parameters of living organisms, the most important source of which is the chemical energy of the molecules within the system. Living organisms are known to produce energy by utilizing the chemical energy of the food they digest. Within a living cell, the concentration of ions and substances differs from the intercellular environment; that is, a concentration gradient exists across the cell membrane. Differences in ion and molecular concentrations are also caused by other gradients, such as osmotic , electrical, filtration, and others.